Penerapan Core Value Berakhlak Asn Dalam Konsepsi Nilai-Nilai Etika Administrasi Publik - Handayani, Wuri; Suryawati, Dina; Rohman, Hermanto (JPAP: Journal of Public Administration Progress, 2025)
This article aims to describe the application of the corevalue of BerAKHLAK ASN in the conception of ethical values ofpublic administration at the East Java Provincial Government andDevelopment Regional Coordinating Agency in Jember (Bakorwil)V Jember. Bakorwil V Jember implements the ASN core value ofhaving morals in accordance with the Circular Letter of theGovernor of East Java Number 800/1456/031.2/2022, the aim ofwhich is as a basic value and work culture for ASN in East Java.The core value of BerAKHLAK is a program that contains a seriesof basic values guidelines and a code of ethics for ASN that areuniform nationally in accordance with the Circular Letter of theMinistry of Empowerment of State Apparatus Bureaucratic Reform(MenPAN RB) Number 20 of 2021. The implementation of the corevalue of BerAKHLAK for ASN is assessed using indicators ofethical values Widodo’s public administration which includes 7indicators, namely efficiency value, value of distinguishing betweenpersonal and office property, impersonal value, crystal systemvalue, responsible value, accountability value and responsivenessvalue. The type of research used in this research is descriptiveresearch with a qualitative approach. The results of the researchshow that from the application of the ASN BerAKHLAK corevalues, five public administration ethical values were found, namelythe values of efficiency, impersonal, ethical system, responsibility,accountability and responsiveness. This shows that theimplementation of the core value of BerAKHLAK ASN in BakorwilV Jember is in accordance with the ethical values of publicadministration even though it does not include all values.